2017
DOI: 10.1002/biot.201700422
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Microbial Metabolite Dynamics and Heterogeneity

Abstract: As yields for biological chemical production in microorganisms approach their theoretical maximum, metabolic engineering requires new tools, and approaches for improvements beyond what traditional strategies can achieve. Engineering metabolite dynamics and metabolite heterogeneity is necessary to achieve further improvements in product titers, productivities, and yields. Metabolite dynamics, the ensemble change in metabolite concentration over time, arise from the need for microbes to adapt their metabolism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 94 publications
0
30
0
Order By: Relevance
“…Tang et al () have reported that global profiles (intracellular, extracellular as well as relevant specific rates) would be in a dynamic concert with glucose availability (feast/famine conditions) induced by feeding strategies (e.g., intermittent feed, feed‐ramp). Thus, new avenues via manipulating metabolite dynamics and cell heterogeneity can be implemented to boost ensemble strain performance (A. C. Schmitz et al, ). Bioreactor scale‐down holds great promise for the generation of actionable knowledge to address the effects of scale‐related factors (Delvigne, Takors, Mudde, van Gulik, & Noorman, ; Wang et al, ).…”
Section: Quantitative Metabolomics and Its Application In Systems Metmentioning
confidence: 99%
See 2 more Smart Citations
“…Tang et al () have reported that global profiles (intracellular, extracellular as well as relevant specific rates) would be in a dynamic concert with glucose availability (feast/famine conditions) induced by feeding strategies (e.g., intermittent feed, feed‐ramp). Thus, new avenues via manipulating metabolite dynamics and cell heterogeneity can be implemented to boost ensemble strain performance (A. C. Schmitz et al, ). Bioreactor scale‐down holds great promise for the generation of actionable knowledge to address the effects of scale‐related factors (Delvigne, Takors, Mudde, van Gulik, & Noorman, ; Wang et al, ).…”
Section: Quantitative Metabolomics and Its Application In Systems Metmentioning
confidence: 99%
“…This reduction of global productivity can often be ascribed to the formation of a specific subpopulation of cells with vanished or discounted production capacity (Delvigne, Zune, Lara, Al‐Soud, & Sorensen, ). It has been recently reported that this cell‐to‐cell heterogeneity arises from metabolic cooperation (Campbell, Vowinckel, & Ralser, ), and metabolite dynamics in response to the extracellular environment plays a vital role in regulating biomass growth and product formation in industrial practices (A. C. Schmitz, Hartline, & Zhang, ). It is hence indispensable to understand how metabolic fluxes are intricately coordinated by complex regulatory mechanisms such as gene‐metabolite association maps (Zampieri & Sauer, ), posttranslational modifications, for example, enzyme phosphorylation or acetylation (Gerosa & Sauer, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently, such non-standard features started to attract the attention of the research community involved in an application of dynamical and stochastic systems theory for modeling macroscopic growth dynamics [21][22][23][24]. The key aim of such research is to connect the revealed genetic/metabolic variability of individual microorganisms with the macroscopic dynamics of the whole population.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…Epigenetic modification is adopted as a switch to regulate some phase variation systems without changing the DNA sequence . Identification of the heterogeneity of a population facilitates a better understanding of microbial stress responses in different environments . The previously applied SMRT methodology, which relies on assessments of average inter‐pulse duration (IPD) values across the whole cell population, cannot reveal epigenetic heterogeneity.…”
Section: Applications Of Smrt Sequencing In Bacterial Epigeneticsmentioning
confidence: 99%